2013
DOI: 10.1021/ef4006719
|View full text |Cite
|
Sign up to set email alerts
|

Premixed Burn Fraction: Its Relation to the Variation in NOx Emissions between Petro- and Biodiesel

Abstract: It is commonly reported in the literature that NO x emissions from a diesel engine increase when fuelling with biodiesel. However, some studies report varying or opposite results. This work scrutinized operating conditions known to yield both increases and decreases in NO x emissions when running on biodiesel. This involved sweeping the injection timing of an instrumented 2 L diesel engine from 14 BTDC (before top-dead-center) to 3 ATDC (after top-dead-center), under loads of 40 Nm and 80 Nm (equating to BMEP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…In several studies, a strong relationship has been observed between the duration of fuel ignition delay (which is affected by fuel molecular structure as discussed in the second section of this paper) and the level of exhaust NO x emissions. 4,10,31,36,37,69 Figure 9 shows the effect of the variation in ignition delay of n -alkanes and 1-alkenes on the exhaust emissions of NO x and the premixed burn fraction at constant injection timing and constant ignition timing. 31 In Figure 9(a), it can be seen that there is a linear increase in the exhaust level of NO x emissions whereas, in Figure 9(b), it is apparent that there is a concurrent increase in the extent of the premixed burn fraction with increasing ignition delay.…”
Section: Influences Of the Fuel Molecular Structure On Engine Exhaustmentioning
confidence: 99%
“…In several studies, a strong relationship has been observed between the duration of fuel ignition delay (which is affected by fuel molecular structure as discussed in the second section of this paper) and the level of exhaust NO x emissions. 4,10,31,36,37,69 Figure 9 shows the effect of the variation in ignition delay of n -alkanes and 1-alkenes on the exhaust emissions of NO x and the premixed burn fraction at constant injection timing and constant ignition timing. 31 In Figure 9(a), it can be seen that there is a linear increase in the exhaust level of NO x emissions whereas, in Figure 9(b), it is apparent that there is a concurrent increase in the extent of the premixed burn fraction with increasing ignition delay.…”
Section: Influences Of the Fuel Molecular Structure On Engine Exhaustmentioning
confidence: 99%
“… 94 This enhancement increases the oxidation rate of the formed fine particles. 94 Also, the absence of aromatics in the RME formulation reduced the activated PM molecules during the accumulation mode. 82 The result obtained (reduction of PM formation during the accumulation mode when the engine is running on RME) is consistent with the findings of refs ( 79 , 103 105 ).…”
Section: Resultsmentioning
confidence: 99%
“…When working with ULSD, the ignition delay period for this fuel is longer and the pre-mixed combustion fraction is larger, which increases the combustion temperature, causing high NO X levels for the low-load condition. Pearce et al confirmed that RME combustion emits lower NO X levels compared to ULSD under the low-load conditions at the pre-mixed combustion fraction condition. However, the exact opposite happens at high loads.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations